A systematic review of adolescent flourishing - Waigel, Nicole Camila (2023)
Traditionally, the study of well-being has been approached from the hedonic and eudaimonic perspectives. However, the last findings suggest that both aspects are complementary, giving place to an integrated conceptualization of well-being called flourishing. In spite of the constant increase of research around this construct, there is still little information regarding flourishing in adolescents. The objective of this study is to review the available literature on flourishing in adolescence in relation to its tie with other constructs, its study in different contexts and the way it has been operationalized. The selection of the studies was conducted in two phases. First, it was verified that the exclusion and selection criteria were met. Then, an evaluation of the quality of the pre-selected studies was carried out. The data were synthesized through the thematic synthesis method. For the results, 28 empirical studies were selected. Four thematic axes were identified: (a) Flourishing in different contexts, (b) Flourishing in regards to other results and positive psychological characteristics and/or their negative counterpart, (c) Flourishing and psychosocial vulnerability, and (d) indicators for the evaluation of flourishing. Suggestions are provided with the goal of consolidating the science of human flourishing.